99 Comparison of Sexual Concerns Between Patients with Prostate Cancer and Their Partners. Issue 1 (1st April 2022) - Loeb, S; Salter, C; Nelson, CJ; Mulhall, JP; Byrne, N; Sanchez Nolasco, T; Ness, M; Gupta, N; Cassidy, C; Crisostomo-Wynne, T; Li, R; Wittmann, D
ABSTRACT: Introduction: Prostate cancer diagnosis and treatment have a significant impact on sexual function and quality of life. Although prostate cancer is often called a "couples disease, " there is limited research on the needs of partners who are affected by the patient's sexual dysfunction. Objective: The objective of our study was to compare the sexual health concerns and unmet needs of patients with prostate cancer and partners using real-world data from an online prostate cancer community. Methods: We performed a mixed-methods analysis of data from the Inspire UsTOO Prostate Cancer Online Support & Discussion Community. This online health community about prostate cancer has more than 30, 000 members, including both patients and partners. Through a data use agreement, we obtained anonymized text from public postings to the Sexual Health & Intimacy Forum on this community. Quantitative and qualitative data were examined from a random sample of 10% of the posts by women about sexual health (n=66), and were compared to an equal number of randomly selected posts by men. Results: Among 6193 posts about sexual health and intimacy in prostate cancer, 661 (11%) were by female contributors. Of posts with cancer treatment details, surgery was the most common treatment discussed followed by hormonal therapy. Erectile dysfunction was the most common sexual complaint for both men and women. Posts by women were most likely to discuss problems with communication, relationship conflict, their partner's loss of libido, and the importance of intimacy. Common themes of the posts included coping with a "new normal" in their relationship, lack of access to and expense of erectile aids, and insufficient information and support from clinicians surrounding sexual recovery. A greater proportion of female posts conveyed emotion compared to male posts. The most common positive emotions were satisfaction and hope; while the most common negative emotions were frustration and loss of familiar sexual interaction. Although many posts discussed a variety of medical and surgical therapies for sexual recovery, very few discussed counseling or other psychosocial treatments. Conclusions: Patients with prostate cancer and their partners experience a wide range of sexual health issues related to prostate cancer diagnosis and treatment. Online communities are widely used to give and receive peer-to-peer advice and support during sexual recovery. These findings highlight an unmet need for more extensive education and support surrounding sexual health for couples during the prostate cancer journey. Disclosure: No